Financial inclusion and its impact on economic growth: Empirical evidence from sub-Saharan Africa - Chuka Uzoma Ifediora; Kenechukwu Onochie Offor; Eze Festus Eze; Samuel Manyo Takon; Anthony Eboselume Ageme; Godwin Imo Ibe; Josaphat Uchechukwu Joe Onwumere (Cogent Economics & Finance, 2022)
This study examines the impact of financial inclusion on economic growth using panel data of 22 sub-Sahara African (SSA) countries during the period spanning from 2012 to 2018. The study employs the system Generalized Method of Moments (GMM). Using a composite index of financial inclusion as well as individual financial inclusion indicators, we discovered that the availability dimension of financial inclusion, penetration dimension of financial inclusion and composite financial inclusion (all indicators put together) significantly and positively impact economic growth while the usage dimension of financial inclusion improves economic growth but not significantly. Also, bank branches and ATMs have positive and significant impact on economic growth, deposit accounts and outstanding loans promote economic growth but not significantly while outstanding deposits adversely affects economic growth. In addition, findings for mobile money indicators from 2012 to 2018 revealed that mobile money agents weaken economic growth while mobile money accounts and mobile money transactions foster economic growth but not significantly. This implies that financial education policies which help Africans better understand the potential benefits of the usage of banking services should be pursued.
Keywords: 330; Financial inclusion; economic growth; principal component analysis; GMM; subSaharan Africa